The effect of processing methods of canola seed on growth performance, blood parameters, liver enzymes, and immune status of broiler chickens - Keyhani, H; Khorshidi, KJ; Jafari, MA (Journal of the Hellenic Veterinary Medical Society, 2025)
Canola meal is a protein source for poultry feeding. Canola has anti-nutritional compounds whose effects can be reduced during processing. The research aim is to investigate the processing methods of canola seed by irradiation, roasting, and enzyme methods on the broiler chicken traits. To experiment, 450 day-old broiler chickens of the Ross 308 strain were placed in 30 pens. Treatments included the control treatment (without canola seeds), the treatment containing raw canola seeds, and 3 treatments processed by enzymes, gamma rays, and roasting methods. Repeat were 6 in all treatments. The traits were growth performance, blood and immune parameters, liver enzymes, and antibody titers against Bronchitis and Gumboro disease. GLM procedure and Duncan's test (α=0.05) by SAS software were used for data analysis and to compare treatment' means, respectively. The processing methods effect was significant (P<0.01) on the protein solubility percentage in KOH, the peroxide number, and the urease activity. Also, the processing methods effect was significant (P<0.05) on the feed consumption in different rearing phases, body weight gains in the starter and grower phases, FCR in all rearing phases, the total protein concentration, uric acid, kidney enzymes, and antibody titers. In general, the gamma radiation and roasting improved the chicken's traits. The canola seed processing increases the absorption of its nutrients by reducing anti-nutrient compounds. Improving antibody titers against Bronchitis and Gumboro diseases is very effective in health management and herd vaccination, and will reduce related costs. Feed processing can change nutrient requirements by influencing activities related to feed consumption.